Temporal and spatial availability of Atlantic Thread Herring, Opisthonema oglinum, in relation to oceanographic drivers and fishery landings on the Florida Panhandle. (15th April 2015) - Chagaris, David; Mahmoudi, Behzad; Muller‐Karger, Frank; Cooper, Wade; Fischer, Keith
Abstract: Since 1995, landings of Atlantic Thread Herring ( Opisthonema oglinum ) on the Florida Panhandle averaged 124 mt each spring (April–June) but declined to nearly zero in 1996–97 and 2006. To elucidate causes of recurring periods of low landings, we used generalized additive mixed models (GAMMs) to examine the relationship between Atlantic Thread Herring catch in a trawl survey on the west‐central coast of Florida and four environmental variables. Chlorophyll‐ a was significant in the models, indicating a direct relationship between local abundance of baitfish and their planktonic food. Temperature and depth were also significant whereas salinity was not. During 2003 and 2012, synoptic satellite‐derived temperature and chlorophyll‐ a maps were used with the GAMMs to predict monthly spatial availability on the Florida Panhandle fishing grounds (long. 85–88 o W and depth 12–25 m). The predicted monthly availability was significantly correlated with commercial catch rates (Pearson's r  = 0.26, P  = 0.004, d.f.   = 118). We used multiple linear regression (MLR) with lags to describe the effect of river discharge and wind (as a transport mechanism) on surface chlorophyll‐ a over the Panhandle fishing grounds. Discharge from local rivers was significant in all MLRs, and the Mississippi was only significant as an interaction with wind. We conclude that Atlantic Thread Herring are distributed over the Panhandle fishing grounds based on food availability that is driven by river discharge and eastward transport of Mississippi River plumes. This analysis improves our understating of baitfish dynamics, an important ecosystem component in the Gulf of Mexico.